2022
DOI: 10.3390/microorganisms10010158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allelochemicals, Soil Enzyme Activities, and Environmental Factors on Rhizosphere Soil Microbial Community of Stellera chamaejasme L. along a Growth-Coverage Gradient

Abstract: Allelochemicals released from the root of Stellera chamaejasme L. into rhizosphere soil are an important factor for its invasion of natural grasslands. The aim of this study is to explore the interactions among allelochemicals, soil physicochemical properties, soil enzyme activities, and the rhizosphere soil microbial communities of S. chamaejasme along a growth-coverage gradient. High-throughput sequencing was used to determine the microbial composition of the rhizosphere soil sample, and high-performance liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…In other words, an intermediate level of disturbance increases the diversity of microbial communities. PLS‐DA analysis further indicated the significant separation of rhizosphere bacterial community at diverse expansion levels, positively consistent with previous studies (Cheng et al, 2022). Plant factors have been proven to have a powerful explanation for changes in the soil bacterial community (Yu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…In other words, an intermediate level of disturbance increases the diversity of microbial communities. PLS‐DA analysis further indicated the significant separation of rhizosphere bacterial community at diverse expansion levels, positively consistent with previous studies (Cheng et al, 2022). Plant factors have been proven to have a powerful explanation for changes in the soil bacterial community (Yu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that many orchid mycorrhizal fungi can promote nutrient absorption in the plant rhizosphere [29]. Meanwhile, they also affect changes in microbial community structures and their functions in rhizosphere soil [30][31][32] . However, the effect of symbiotic fungus Armillaria on the absorption of nutrition elements by G. elata Bl.…”
Section: Introductionmentioning
confidence: 99%
“…Proteobacteria was found to be the most dominant endophytic phylum in S. chamaejasme in both culturedependent and independent studies. Similarly, Jin et al (2018) and Cheng et al (2021) found that Proteobacteria was the dominant endophytic phylum in roots of S. chamaejasme from different elevation gradients. This is consistent with previous findings that Proteobacteria is widespread in the soil, marine, surface water and plant (Spain et al, 2009;Becerra-Castro et al, 2016;Timmermans et al, 2017;Dang et al, 2020).…”
Section: Discussionmentioning
confidence: 83%